Deploying effectively dispatchable PV on reservoirs: Comparing floating PV to other renewable technologies. (1st November 2018) - Perez, Marc; Perez, Richard; Ferguson, Craig R.; Schlemmer, James
Highlights: Floating PV is a more effective lake-based power generation resource than evaporation engines. Covering 1.2% of US reservoirs with floating PV produces more energy than installed hydropower. With an area equal to US reservoirs, PV could produce 100% US electricity on a firm 24/7/365 basis. Replacing hydropower with floating PV would let dam operators focus on water management issues. Abstract: In this article, we present a detailed simulation of floating photovoltaic's (PV) energy yield and associated evaporation reduction potential for the largest 128 US hydropower reservoirs. A recent article by Cavusoglu et al., published in the journal Nature Communications, outlined a hypothetical evaporation engine that could harness the energy of lake water evaporation while simultaneously conserving the water resource. Its authors suggest that evaporation engines deployed across all US lakes and reservoirs could, collectively, yield up to 70% of the total U.S. electricity production. We show that floating PV technology could: (1) deliver considerably more electrical energy than evaporation engines, amounting to 100% of the US production with only a fraction of the lakes; (2) deliver this energy on a firm, effectively dispatchable basis; and (3) conserve as much water as the evaporation engines.